Attapulgite modified magnetic metal-organic frameworks for magnetic solid phase extraction and determinations of benzoylurea insecticides in tea infusions. (1st July 2020) - Niu, Mingxin; Li, Zuopeng; He, Wenjuan; Zhou, Wenfeng; Lu, Runhua; Li, Jing; Gao, Haixiang; Zhang, Sanbing; Pan, Canping
Highlights: ATP@Fe3 O4 @ZIF-8 were synthesized as magnetic solid phase extraction adsorbent. The extraction conditions were optimized for quantification of benzoylureas. Rapid and efficient extraction with good recycling stability. The method was applied for determination of benzoylureas in tea infusions. Abstract: Herein, we developed a novel magnetic solid phase extraction method based on attapulgite-modified magnetic metal-organic frameworks (ATP@Fe3 O4 @ZIF-8), and this method could be used for the determination of benzoylureas when it was coupled with high-performance liquid chromatography. The established method was validated in terms of linearity (2.5–500 μg L −1, with correlation coefficient (R 2 ) > 0.9994), accuracy (with satisfactory recovery of 88.29–95.99%) and precision (with relative standard deviation (RSD) of less than 8%). In addition, the enrichment factors (EF) ranged from 63.6 to 72.2. Limit of detection (LOD) and limit of quantitation (LOQ) were 0.7–3.2 μg L −1 and 2.3–10.7 μg L −1, respectively. Moreover, there was hardly any noticeable loss of the extraction efficiency when this extraction method undergoes five cycles. Finally, this method was successfully used for the determination of six benzoylureas in different tea infusions and the determined relative recoveries ranged from 78.8 to 114.3%.